IT - Based Mathematics Learning Module To Decrease Students’ Mathematical Anxiety: Modul Pembelajaran Matematika Berbasis IT untuk Mengurangi Kecemasan Matematika Siswa - Istikomah, Endang; Herlina, Sari; Nurmaliza, Nurmaliza (Universitas Wiralodra, 2022)
The purpose of this study was to determine the level of students' mathematics anxiety and student learning outcomes after using the PMB IT module. The type of this research is Pre-Experiment with One Group Pretest-Posttest design. The instruments used are student mathematics anxiety questionnaire sheets and student response questionnaires, while student learning outcomes can be seen after the UAS exam. The data analysis technique used is qualitative and quantitative data analysis. For data processing, the writer used SPSS 16 software and Microsoft Excel 2013. The students' mathematical anxiety data obtained were analyzed descriptively and student learning outcomes data were processed using Inferential Statistics One-Sample T-Test. The results showed that the level of students' mathematics anxiety after using the PMBIT module decreased by an average of 11.55. While the level of students' mathematics anxiety after using the module in the low, medium, and high categories, respectively, was 40.5%, 56.8%, and 2.7%. Furthermore, there is an increase in student mathematics learning outcomes using the PMBIT Module with sig. 0.029 and a mean of 81.59